Spatial representation and learning in real and virtual environments - Luo, Zhiqiang (2008)
Few things are as fundamental to the human experience as spatial navigation in the real and virtual environments. People navigate in environments by extracting ambience information, forming a mental representation, and in turn employing that mental representation for route planning and maneuvering. Crucial for spatial navigation, mental representation of the environment, namely spatial representation, is the internalized reflection and reconstruction of environment in thought. Meanwhile, the acquisition of accurate and complete mental representations, referred to as spatial learning, is much affected by human’s egocentric experience within the environment together with various environment characteristics. This research aims to understand the cognitive processes of building appropriate mental representations of the environment. In particular, this research investigates the spatial representations acquired in a 3D room environment as well as in a multilevel building. Human egocentric experience is operationalized based on varying exocentric views according to either watching from different exocentric perspectives or learning from 3D maps. Also reckoned are environmental characteristics including the environmental geometry and complexity. Four studies are conducted systematically to justify hypotheses of spatial representation and learning with respect to different egocentric experiences and environment characteristics. The results reveal that (1) Spatial information on the horizontal and vertical dimensions of the environment is encoded and represented in terms of different frames of reference regarding spatial navigation; (2) The exocentric views associated with an exocentric perspective or a 3D map facilitate the acquisition of survey knowledge, instead of route knowledge, of the environment; and (3) Spatial representation inherently preserves specific biases, regardless of egocentric experiences and environment characteristics.